Molecular Detection of Canine Distemper Virus in Dogs in Baghdad Province, Iraq - Mansour, Khalefa A; Hasso, Saleem A (The Iraqi Journal of Veterinary Medicine, 2021)
Canine distemper (CD) is an infectious disease that affects dogs and is extremely contagious and lethal, with a high mortality and morbidity rates. It infects a broad variety of animals, including primates, cetaceans, and carnivores causing a multi-systemic pathological condition. This study aimed to detect canine distemper virus (CDV) in blood samples of dogs clinically suspected with distemper at the Baghdad Veterinary Hospital, Baghdad, Iraq. CDV nucleoprotein gene (N) was detected in the whole blood of 46 dogs using reverse transcription-PCR (RT-PCR). The partially amplified (591 bp) fragment of the N gene was detected in 12 of 46 (26%) blood samples of dogs examined. Based on the partial sequencing data of the N gene, three local isolates might be similar to the NCBI-BLAST reference CDV virus isolates FJ977579.1 China, AF378705.1 USA, and AF305419.1 UK, while other strains EU072200.1 Hungary, AF164967.1 Switzerland, KU578257.1 Germany, and AB474397.1 Japan were found to be rather distinct. The isolates displayed a higher level of similarity with the Snyder Hill CDV strain and Onderstepoort CDV strain. There was less homology with the CDV strain A75/17 of Switzerland and 007Lm CDV strain of Japan. In conclusion, this study confirmed that CDV infection is present in domestic dogs in Iraq. This may indicate a risk of the disease spreading to parts of the country that may be disease-free.